The Influence of Mass Media on the Formation of Spiritual and Aesthetic Values as a Factor of Supporting the Vitality of Modern Youth: A Sociological Aspect - Chutova, Natalia; Pohorzhelskyi, Ihor (Educological discourse, 2026)
The article examines the problem of the influence of mass media on the formation of spiritual and aesthetic values in modern youth, which are essential resources for developing and maintaining resilience, overcoming stress, and maintaining emotional and cognitive stability in challenging circumstances. The purpose of the theoretical analysis is to substantiate the importance of the spiritual and aesthetic culture of youth in a dynamic society and the role of the mass media in the formation of spiritual values in today's conditions. To achieve this purpose, classical sociological, social-psychological works, the results of sociological research that reflect the stated issues, as well as analysis and logical generalisation, were used. It has been found that in society, spiritual and aesthetic culture is often perceived as impractical and secondary, although it determines the nature of society's life and is necessarily present in any material sphere of life, being its qualitative characteristic. It is clarified that modern mass media, the centre of which is Internet technologies/social media, is a powerful translator of a large volume of various information, which creates conditions for self-development, self-education, it is in great demand in the youth environment, but, on the other hand, it is a specific social actor that spreads the values of mass culture, destroys traditional spiritual and aesthetic sensibility, replicates, reproduces simple thoughts, feelings, images that are surrogates of spiritual culture, where ideals turn into clichés, which creates spiritual and moral deafness. It is determined that human spirituality is a resource for the vitality of society; however, the moral and aesthetic culture of modern youth is formed against the backdrop of the absence of unified basic values, the struggle of the media with traditional socialisation institutions, and the loss of spiritual connection with previous generations. Young people are in an aggressive information environment, where the strategy of hedonism and consumption is often demeaned as a form of spiritual search. As a result, mutations and changes occur in the youth hierarchy of values, and the sense of adequate assessment of the social situation is dulled, leading to a decrease in vitality. It is proposed to form a new educational dialogic media strategy and implement promising projects that will ensure effective socialisation, promote the development of moral ideals, and help understand difficulties as opportunities for self-development and self-improvement. It is proposed to consolidate efforts to neutralize the destructive influence of the mass media on the youth audience, to ensure constructive public control over the information flow, to mobilize sociologists, teachers, psychologists, and media industry workers to develop new principles of media education policy, to create media products of educational orientation that would contribute to psychological support, the development of aesthetic ideals, which teach a person to understand difficulties as an opportunity for self-development and self-improvement.